Can regional environmental quality improve green innovation performance? an empirical analysis from China - Ding, Zijing; Li, Chen (Frontiers in Environmental Science, 2023)
Introduction: Green innovation is an important driving force for reducing pollution and achieving high-quality development. Environmental factors are important external variables that affect innovation and are crucial to innovation development. There is a close relationship between environmental quality and green innovation performance. This paper takes the single environmental factor and combination of environmental factors of environmental quality heterogeneity as the explanatory variables, the traffic scale, economic scale, industrial scale and consumption scale as the control variables, and the per capita GDP of each city as the threshold variable, and calculates the impact of the single environmental factor and combination of environmental quality factors on the green innovation performance of 286 cities in China under different per capita GDP thresholds.We used Data Envelopment Analysis (DEA) and Threshold Regression model to measure the relationship between environmental quality and green innovation.(1) under different thresholds, a single environmental factor has different impacts on the comprehensive level of innovation drive in Chinese cities. Comparing the single environmental factor under different threshold values of per capita GDP, when the per capita GDP is low, attention should be paid to improving the centralized treatment rate of urban sewage treatment plants and the comprehensive utilization rate of general industrial solid waste; When the per capita GDP is high, the harmless treatment rate of domestic waste, the centralized treatment rate of sewage treatment plants, the green coverage rate of the built-up area, and the green area can all have different promotion effects on the driving capacity of cities along the line. (2) Under different thresholds, the elasticity coefficient of the total ecological environment, the total ecological environment has a relatively obvious promoting effect on the innovation-driven development of cities along the line, but this promoting effect shows a further weakening trend with the increase of per capita GDP.This study helps to explain environmental quality and green innovation, which is important for promoting sustainable economic development. The government should control environmental pollution and introduce laws and policies to ensure innovation.